Public relations: Komunikasi mempengaruhi loyalitas pelanggan usaha jasa laundry - Mawada, Alifia Aulia (Maliki Interdisciplinary Journal, 2023)
New Daily Laundry is a laundry business that has been operating in Malang for 5 years. Located behind the Negrei Islamic University of Maulana Malik Ibrahim Malang, New Daily Laundry competes with two competing outlets around the campus. Through good communication and quality service, this business has managed to maintain customer loyalty and win trust in the midst of increasingly fierce competition. By using customer feedback, New Daily Laundry ensures that customer needs and preferences are well met. The success of New Daily Laundry shows that the right communication strategy is the key to surviving in the midst of intense market competition.